Molecular Identification and Susceptibility Pattern of Clinical Nocardia Species: Emergence of Nocardia crassostreae as an Agent of Invasive Nocardiosis - Saad J Taj-Aldeen; Anand Deshmukh; Sanjay Doiphode; Atqah Abdul Wahab; Mona Allangawi; Ahmed AlMuzrkchi; Corné H Klaassen; Jacques F Meis (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Nocardia species are rare, opportunistic organisms that cause disease in both immunocompetent and immunocompromised individuals.